Magnetospheric Multiscale Observations of ULF Waves and Correlated Low‐Energy Ion Monoenergetic Acceleration. Issue 4 (24th April 2019) - Li, B.; Han, D.‐S.; Hu, Z.‐J.; Hu, H.‐Q.; Liu, J.‐J.; Dai, L.; Liu, H.; Escoubet, C. P.; Dunlop, M. W.; Ergun, R. E.; Lindqvist, P.‐A.; Torbert, R. B.; et al.
Abstract: Low‐energy ions of ionospheric origin with energies below 10s of electron volt dominate most of the volume and mass of the terrestrial magnetosphere. However, sunlit spacecraft often become positively charged to several 10s of volts, which prevents low‐energy ions from reaching the particle detectors on the spacecraft. Magnetospheric Multiscale spacecraft (MMS) observations show that ultralow‐frequency (ULF) waves drive low‐energy ions to drift in the E × B direction with a drift velocity equal to VE × B, and low‐energy ions were accelerated to sufficient total energy to be measured by the MMS/Fast Plasma Investigation Dual Ion Spectrometers. The maximum low‐energy ion energy flux peak seen in MMS1's dual ion spectrometer measurements agreed well with the theoretical calculation of H + ion E × B drift energy. The density of ions in the energy range below minimum energy threshold was between 1 and 3 cm −3 in the magnetosphere subsolar region in this event. Plain Language Summary: Low‐energy ions of ionospheric origin dominate most of the volume and mass of the terrestrial magnetosphere. The amount of low‐energy ions that exist and the way they are distributed are open areas of study important to understanding the magnetized plasma environment surrounding Earth. Magnetospheric Multiscale spacecraft (MMS) is a four‐spacecraft mission carrying numerous instruments for characterizing the particles and fields making up this environment and which can be applied to investigating low‐energy ions. In this study, we found an event based on the MMS data showing that ultralow‐frequency waves drive low‐energy ions to drift in the direction normal to the plane defined by the electric and magnetic fields. This charged particle motion is called the E × B drift. During this event, the observations taken by the MMS from a distance of 64, 000 km in space were consistent with the theoretical calculation of the charged particle E × B drift. The results were applied to show density of low‐energy ions in the subsolar magnetosphere region during this event was in the range of 1 to 3 cm −3 . This event provides evidence for the E × B drift action based on magnetospheric particle and field observations that can be further applied to detect low‐energy ions in other magnetospheric locations. Key Points: An ultralow‐frequency wave and correlated low‐energy ion monoenergetic acceleration was observed by MMS1 The maximum ion flux energy level detected by MMS1 DIS agreed well with the theoretical calculation of H + ion E × B drift energy The density of low‐energy ions with energy below minimum energy threshold was between 1 and 3 cm −3 in the magnetosphere subsolar region